Modernization and the evolution of irrigation practices in the Rio Dulce Irrigation Project, Santiago del Estero, Argentina : una tarea de todos - Prieto Garra, Daniel (Wageningen University, 2020)
Tesis para obtener el grado de Doctor of Philosophy (PhD), de la Wageningen University, en 2006